Tomhændet må ingen se mit ansigt! Gavens teologi i Det Gamle Testamente - de Hemmer Gudme, Anne Katrine (Dansk Teologisk Tidsskrift, 2015)
The Theology of the Gift in the Hebrew Bible. This article promotes an understanding of sacrifices in the Hebrew Bible as foodgifts to Yahweh. It is claimed that a proper understanding of gift-giving as an open-ended social practice that establishes lasting relationships between the exchanging parties can help us understand the role and function of sacrifices in the Hebrew Bible. In light of this, sacrifices as food for Yahweh, child sacrifice and the prophetic cult criticism are discussed.